Kemampuan Representasi Matematis Siswa SMP dalam Menyelesaikan Soal Cerita Aljabar - Hidayah, Shofia (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2022)
Mathematical problems that are closely related to everyday life are usually presented in the form of a story, which is referred to as a word problem. Completing math word problems is not just answering questions; it also requires students' ability to understand the problem, model a problem into a mathematical sentence, and perform calculations with appropriate mathematical rules. Solving word problems is closely related to mathematical representations. This research is qualitative and aims to describe the ability of students' mathematical representations to solve algebraic story problems. This research involved 16 grade VII students of the Integrated Islamic Middle School Permata Kraksaan Probolinggo. The instruments used in this study were the test questions for the ability to represent mathematical representations and interview guidelines. The subjects in this study were three students, each representing high, medium, and low cognitive ability. The conclusion of this study is that mathematical representation in the aspect of visual representation can be achieved by subjects with high and medium cognitive abilities. The ability to use mathematical representation in the aspect of symbolic representation can be achieved by subjects with high cognitive abilities. The ability of mathematical representation in the verbal aspect has not been achieved by the three subjects because they have not been able to interpret the numbers obtained in solving the problems into words. The reason was because the three subjects were not used to writing final conclusions in the form of words after solving problems.